Association between Late Manifestations of Testicular Dysgenesis Syndrome and Anogenital Distance: A Systematic Review and Meta-analysis - Carolina Arissa Tsutida; Ana Carolina Bernard Veiga; Anderson Joel Martino-Andrade; Diancarlos Pereira de Andrade; Rosiane Guetter Mello; Juliane Centeno Müller (Journal of Human Reproductive Sciences)
Background: In 2001, Skakkebæk et al. proposed that certain male reproductive disorders might be grouped into a syndrome called testicular dysgenesis syndrome (TDS), as they all appear to be associated with disruption of the embryonic and foetal programming of gonadal development. TDS may be manifested in early life by the presence of genital malformations (hypospadias and cryptorchidism) and in adult life as disorders represented by low sperm counts and testicular cancer. Changes in androgen hormones during the foetal development, in addition to resulting in TDS, can also cause permanent changes in anopenile anogenital distance (AGDap) and anoscrotal anogenital distance (AGDas). Aims: The objective of this study was to determine whether there is a relationship between late manifestations of TDS and reduced anogenital/anoscrotal distance. Materials and Methods: The present study is a systematic review and meta-analysis. The research included papers from 2001 to 2020, comprising a total of 737 articles, and 13 articles were selected. Results: Linear regression analysis was performed to evaluate the relationship between the two anogenital distance measures, which showed a significant positive association (P = 0.039). A meta-analysis was also performed and compared AGDap and AGDas between control and case groups, with cases defined as men with any late TDS manifestation. These data showed a significant reduction in AGDas in the affected population (P = 0.04), but no differences in the AGDap measure (P = 0.59). Conclusion: Our study confirmed a significant relationship between reduced AGDas and late manifestations of TDS, providing further support to the association between prenatal androgen deficiency and late-onset reproductive disorders.